Recent Advances in Non-pharmacological Behavior Management Technique in Children - Tirtharaj Brahma (Indian Journal of Forensic Medicine & Toxicology, 2020)
A conventional communication along with a caring attitude develops an affinity with a pediatric patient.Non-pharmacological behavior modification approach allows pediatric dentists the ability to effectivelyalleviate behavioral issues by balancing their preference of treatment with that of the child’s type of mutualpractice. Whereas Activity informed adult patients with dental phobias is the product of an offensiveapproach employed in childhood. Hence to overcome these disadvantages newer non-pharmacologicaltechniques were handled by Pediatric Dentists which provided long term reinforcement in younger children.This review will focus on reckoning the recent advances in non-pharmacological behavior managementtechniques in children.